Penilaian Postur Kerja Pada Pekerja Bagian Penggorengan Keripik - Iva Mindhayani; Suhartono Suhartono (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
The postures of frying workers when they do their activities are back bent, the body twists to the right and left, and the arm reachs too wide. The work activities are putting slices of tempe in a frying pan, and frying and draining tempe. From the interview, we know that workers felt the most pain in the buttocks/thighs and back. The pain happens because workers do their activities in a static position for a long time. It causes complaint to the skeletal muscle system. The purpose of this study are to find out the complaints that felt by workers, find out the work posture in accordance with ergonomics rules or not, and find out how big the level of risk is. The methods used in this study were Nordic Body Maps (NBM) questionnaire, Rapid Upper Limb Assessment (RULA) method and Rapid Entire Body Assessment (REBA) method. The results of the analysis using the NBM questionnaire showed that 50% workers felt pain in their shoulders, 50% in their lower back,60 % in their buttocks/thighs, and 50% in their knees. The second conclusion of the NBM questionnaire was the work posture of frying workers did not match with the ergonomics rules. The results of the RULA assessment shows the work activity of the frying department was 7. This level was very high level, while the results of the REBA assessment show a very high risk with a score of 11. Further actions needed are investigating and immediating change actions. Improvements that can be made for workers are using a chair with a backrest, doing stretching movements to reduce the pain felt in the limbs, and rearranging the work area. Keywords: work posture at frying station, Nordic Body Maps, RULA, REBA